Frontal Cortex Function. - Buchsbaum, Monte S. (American Journal of Psychiatry, 2004)
The writer discusses the diverse functions performed by the frontal cortex and notes the impact of injury to this area of the brain or deficits to its function. Two illustrations that portray the frontal cortex from MRI tracings shown within the brain structure and demonstrate connections between the frontal cortex and thalamus by way of the internal capsule developed from diffusion tensor imaging are provided. It is contended that these newest type of brain imaging technologies facilitate the acquisition of structural, functional, and chemical imaging from the human brain in vivo.